Zapisz podane wyrażenia bez nawiasów. tam gdzie jest to możliwe , uprość wyrażenia.
a) -(-x) + (-3) =
b) -(-2x) - 5 - 3x =
c) -(16x + 3) + (3 - x) =
d) x - ( -15x + 9)x =
e) -(-(-21x) + 6)) =
f) (-4x) * (-3) + 2x - 1=
g) (-7x) * (-3x) + 4 - 19x =
h) 16x : (-4) + 1 - 5x =

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-02-28T10:15:35+01:00
A) -(-x) + (-3) = x-3=0 x=3
b) -(-2x) - 5 - 3x = 2x-5-3x=0 -x=5 x=-5
c) -(16x + 3) + (3 - x) =-16x -3 +3 -x=0 -17x=0 x=0
d) x - ( - 15x + 9)x = x- 15x^2 + 9x
e) -(-(-21x) + 6)) =-21x +6
g) (-7x) * (-3x) + 4 - 19x = 21x^2 +4 -19x
2 5 2